Sistem Pemeliharaan Suhu Kandang Ayam Boiler pada Umur 0 – 30 Hari Menggunakan Arduino UNO - Epa Rosidah Apipah; Aryo Nurman Wardhana; Nining Yulianingsih; Audi Murfi Siregar; Hasan Hasan; Dadang Hidayat (Lembaga Pengembangan Kinerja Dosen, 2025)
Maintaining stable cage temperature is a crucial factor in the success of broiler chicken farming, especially in close house systems that rely on optimal microclimate control. Temperature instability can lead to thermal stress, reduced growth rates, and increased mortality in broilers, particularly during the early stages of life (0 to 30 days old). This study aims to design and implement an automatic temperature control system based on the Arduino Uno microcontroller integrated with a DHT11 temperature and humidity sensor in the broiler chicken cages of PT. Barokah Restu Utama. The system is designed to read temperature and humidity in real-time and automatically activate or deactivate cooling devices such as fans or heating devices like incandescent lamps, depending on the temperature range required for each growth phase. The ideal temperature range used as a reference in this system includes 30–32°C for chickens aged 0–7 days, 29°C for ages 8–14 days, 28°C for ages 15–21 days, and 26–27°C for chickens aged 22–30 days. Testing results show that the system is capable of maintaining stable temperatures according to the specified standards for each growth phase. With this automatic control system in place, broiler chicken maintenance becomes more efficient and effective. The risk of mortality due to heat stress is significantly reduced, and chicken growth becomes more optimal. This technology offers a practical and economical solution, especially for small- to medium-scale broiler chicken farmers who use close house systems. The system is easy to operate and relatively affordable to install, making it an accessible innovation that supports better livestock management through automation and smart farming practices.